DISEÑO DE UN MINIGENERADOR HIDROELÉCTRICO PARA GENERACIÓN DISTRIBUIDA - MORAN LOOR, DOUGLAS JAMINTON (2025)
The goal was to harness the energy of water flow to generate electricity efficiently and sustainably, presenting a viable solution for improving access to electricity in remote areas